Jews, Judaism, and the Reformation in sixteenth-century Germany - Bell, Dean Phillip, 1967-; Burnett, Stephen G. (Studies in Central European histories, 2006)
This book represents a multi-disciplinary approach to the problem of the Jews and the German Reformation. The contributions come from both senior and emerging scholars, from North America, Israel, and Europe, to ensure a breadth in perspective. The essays in this volume are arranged under four broad headings: 1. The Road to the Reformation (late medieval theology and the humanists and the Jews), 2. The Reformers and the Jews (essays on Luther, Melanchthon, Bucer, Zwingli, Calvin, Osiander, the Catholic Reformers, and the Radical Reformers), 3. Representations of Jews and Judaism (the portrayal of Judaism as a religion, images of the Jews in the visual arts, and in sixteenth-century German literature), and 4. Jewish Responses to the Reformation. Contributors include: Dean Phillip Bell, Jay Berkovitz, Robert Bireley, Stephen G. Burnett, Elisheva Carlebach, Achim Detmers, Yaacov Deutsch, Maria Diemling, Michael Driedger, R. Gerald Hobbs, Joy Kammerling, Thomas Kaufmann, Hans-Martin Kirn, Christopher Ocker, Erika Rummel, Petra Schöner, Timothy J. Wengert, and Edith Wenzel.